Notion of Prejudice in the Works of Immanuel Kant - Pedro Jesús Teruel (Anales del Seminario de Historia de la Filosofía, 2014)
The notion of prejudice occupies a not very visible place in the Kantian works. In fact it has been seldom treated in Kantian studies in German, English, French, Italian or Spanish. But it connects with relevant key notes of the Critique of Pure Reason (1781, 1787) as well as from the Critique of Practical Reason (1788) and the Critique of Judgement (1790). The aim of this paper consists in the analysis of the Kantian notion of prejudice, its systematic place and its sources (among these particularly the works of Georg Friedrich Meier and the thought of Christian Thomasius).